Moral Disengagement in Sports: A Study on Young Turkish Athletes - Adnan Ersoy; Ceren Gümüşgül (Türk Spor ve Egzersiz Dergisi)
Ethics in sports are the rules that comply with the spirit of sports and should not be forgotten and very important by all stakeholders. Athletes, coaches, managers, spectators, referees, sports media and many people are the subject of ethical rules in sports. The aim of this study was to investigate moral disengagement attitudes of participants studying at School of Physical Education and Sports and practising active sports. Totally, 310 active athletes (235 male, 75 female) were taken part in this research. Data was gathered through Moral Disengagement in Sport Scale-Short version which was developed by Boardley and Kavussanu (5) and translated to Turkish Language by Gurpinar (19). In evaluation part for questionnaires answered by participants, Kolmogorov Smirnov normality test, T-Test and One Way ANOVA tests were used. According to the results, it was statistically determined that there were not significant differences on age, branches and training years (p gt;0,05); but there were significant differences on analyses done for gender and participants’ mothers’ education level (p lt;0,05). In the light of the obtained results, the importance of increasing sports ethics education and fair-play awards at an early age was emphasized. Fair-play samples should be increased and good behaviours in sports should be seen more.